Model test on development characteristics and displacement variation of water and mud inrush on tunnel in fault fracture zone - Zhang, Qingsong; Jiang, Qichen; Zhang, Xiao; Wang, Deming (Natural hazards (Dordrecht), 2019)
The fault fracture zone, featuring a variety of fault rocks and associated fissures, is a special area which bears the most concentrated stress when it forms and develops. It is always observed to reserve abundant underground water when buried deeply. Therefore, the tunnel under construction is subject to serious water and mud inrush when excavated through this area. In order to study the characteristics of that disaster, a three-dimensional geological model test system was established. Based on a large number of comparisons on materials and tests on mechanical performance, a set of new fault and common surrounding rock materials applicable to the fluid–solid coupling model test were developed. Then, the experimental data were compared with the actual data of the inrush disaster of fault F2 in Yonglian Tunnel, to explore the variation of characteristic parameters such as the location of the inrush, the mass of emission properties, displacement and settlement. As the results showed, the location of the initial inrush occurred at the spandrel of the tunnel face, the mass of emission properties increased with proceeding time, but there was a sudden saltation of the increasing rate when the disaster occurred. Besides, the shape of surface subsidence above the location of the inrush gradually transferred from “W” to “V,” and the subsidence area eventually showed a parabolic pattern. Finally, the conclusion of the model test may shed light on the catastrophic process and evolution law of the water and mud inrush in fault fracture zone.